Review: Analisis Senyawa Obat Warfarin dalam Plasma Darah dengan Metode HPLC/KCKT - Siti Nafisa; Siti Rohmah; Yumareta Anggun Nihan; Lina Nurfadhila; Marsah Rahmawati Utami (Journal of Pharmaceutical and Sciences, 2023)
Warfarin is a synthetic derivative of coumarin whose use as an oral anticoagulant generally used to prevent and treat blood clots, prophylaxis also the treatment of pulmonary embolism, and thrombosis of venous, prophylaxis and treatment prophylaxis of thromboembolic complications from atrial fibrillation or replacement of heart valve, and the risk of death from recurrent myocardial infarction, and thromboembolic events after myocardial infarction can be reduced. Warfarin is a narrow therapeutic index of oral anticoagulants where if there is a slight change in the level of warfarin in the blood, a change in the effective response can occur. Many analytical techniques have been developed for the analysis of warfarin levels in blood plasma, for example using High-Performance Liquid Chromatography coupled with ultraviolet/fluorescence detection, SFC-MS/MS, LC-MS/MS, CZE with ultraviolet detection, and MEKC-ESI–MS. The test method used for monitoring this Review Article has the purpose of reviewing and comparing analytical methods/detection techniques used for the analysis of warfarin in blood plasma. The HPLC method has several advantages in the analysis of warfarin drug levels, such as ease, accuracy, effectiveness of analysis time, and advantages of high sensitivity and selectivity.